2020
DOI: 10.24252/asma.v2i2.17245
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Senam Otak Dalam Meningkatkan Fungsi Memori Jangka Pendek Pada Anak

Abstract: AbstrakTujuan studi ini untuk mengetahui secara teoritik peranan senam otak dalam meningkatkan fungsi memori jangka pendek (short term memory) pada anak. Penelitian kualitatif jenis studi kepustakaan ini dilakukan dengan mengumpulkan berbagai sumber dari jurnal dan buku terkait dengan fokus kajian. Analisis data yang digunakan berupa analisis naratif deskriptif. Hasil penelusuran menunjukkan gerakan yang dilakukan dalam senam otak dapat meningkatkan fungsi memori jangka pendek yang terbukti dengan kemajuan kem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Several previous studies have found that applying brain gyms positively affects a person's academic ability, focus, and balance of abilities (Mendrofa et al, 2020;Widanti & Anjasmara, 2021). Brain gym therapy can also help reduce stress, encourage relaxation, maximize brain function, improve memory, and improve body balance (Damayanti et al, 2020). The many good benefits of brain gyms can increase the focusing ability of medical students class of 2019 who are running online learning during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have found that applying brain gyms positively affects a person's academic ability, focus, and balance of abilities (Mendrofa et al, 2020;Widanti & Anjasmara, 2021). Brain gym therapy can also help reduce stress, encourage relaxation, maximize brain function, improve memory, and improve body balance (Damayanti et al, 2020). The many good benefits of brain gyms can increase the focusing ability of medical students class of 2019 who are running online learning during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Research from [46] that physical activity carried out regularly will improve blood circulation to the brain which will result in an increase in brain intelligence due to a large supply of oxygen. This is reinforced by the results of research from [47] that providing a physical activity stimulus that involves coordination in children can improve brain function and relax the body so that enthusiasm in learning can increase learning achievement.…”
Section: Discussionmentioning
confidence: 99%
“…warna memiliki efek yang lebih kuat terhadap bentuk dan mampu memproduksi level perhatian yang lebih tinggi. Warna merah dipilih karena warna merah merupakan warna yang menarik dan emotif, serta dapat memberi efek yang menyenangkan (Damayanti et al, 2020) Anak membangun pemahaman dan pengetahuan mereka sendiri (Pionika et al, n.d.). Setelah penerapan terdapat penambahan menjadi 5 anak, sedangkan 2 anak lainnya masih kesulitan menggunakan lambang bilangan jika lambang bilangan tidak di urutkan atau diacak.…”
Section: Hasil Dan Pembahasanunclassified